Impact of Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors on Lipoprotein(a) - Frederick Berro Rivera, MD; Sung Whoy Cha, MD; Cruz Linnaeus Louisse, MD; Genquen Philip Carado, MD; John Vincent Magalong, MD; Vincent Anthony Tang, MD; Mary Grace Enriquez, MD; Martha Gulati, MD, MS; Byambaa Enkhmaa, MD, PhD; Neha Pagidipati, MD, MPH; Nishant P. Shah, MD (JACC: Advances)
Background: Lipoprotein(a) [Lp(a)] has been independently associated with increased cardiovascular risk. Objectives: The authors examined the effect of monoclonal antibody proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9is) on plasma Lp(a) levels across multiple trials. Methods: Studies were retrieved comparing the effect of PCSK9i vs placebo on Lp(a) levels. The primary outcome was percent change in Lp(a) levels. Factors associated with the treatment effect were determined by meta-regression analysis. Subgroup analyses were done to explore potential treatment effect differences. Results: PCSK9i reduced Lp(a) levels on average of −27% (95% CI: −29.8% to −24.1%, P < 0.001). Factors associated with the treatment effect included mean percent change in low-density lipoprotein cholesterol (P = 0.003, beta coefficient 0.34, 95% CI: 0.11-0.57, tau2 = 94.8, R2 = 11.82) and apolipoprotein B (P < 0.002, beta coefficient 0.4, 95% CI: 0.14-0.64, tau2 = 93.68, R2 = 11.86). Subgroup analyses revealed consistent treatment effect amongst comparators vs placebo: −27.69% (95% CI: −30.85% to −24.54%, P < 0.001), vs ezetimibe: −24.0% (95% CI: −29.95% to −18.01%, P < 0.001), type of PCSK9i, evolocumab: −29.35% (95% CI: −33.56% to −25.14%, P < 0.001) vs alirocumab: −24.50% (95% CI: −27.96% to −21.04%, P < 0.001), and presence of familial hypercholesterolemia: −25.63% (95% CI: −31.96% to −19.30%, P < 0.001 vs no familial hypercholesterolemia: −27.22%; 95% CI: −30.34% to −24.09%, P < 0.001). Varying treatment effects were noted in the duration of treatment (12 weeks or shorter: −32.43% [95% CI: −36.63% to −28.23% vs >12 weeks: −22.31%] [95% CI: −25.13% to −19.49%, P < 0.001]), P interaction < 0.01. Conclusions: PCSK9is reduce Lp(a) levels by an average of 27%. Mean percent change in low-density lipoprotein cholesterol and apolipoprotein B were associated with treatment effect.